Estado del arte de la educación jurídica, a diez años del Congreso Nacional de Sociología Jurídica - González, Manuela G. (2011)
A collection of one hundred and forty eight (148) papers presented by two hundred and sixty (260) authors, members of the Teaching of Law Groups, at eleven National Legal Sociology Congresses were analyzed. The following questions were made: 1. Which are the elements which contribute to define the field? The writers themselves, their performance at the University Research Groups and the appraisal of their interdisciplinary work. 2. Which has been the authors' starting point? Their themes, problems, declared aims, assumptions and methodological choices. Summing up, the goal is showing an updated picture of available knowledge in the field and throwing a new light into the participant's concerns.